A multi-year and high-resolution inventory of biomass burning emissions in tropical continents from 2001–2017 based on satellite observations. (10th October 2020) - Shi, Yusheng; Zang, Shuying; Matsunaga, Tsuneo; Yamaguchi, Yasushi
Abstract: Biomass burning in the tropics significantly impacts the regional and global atmospheric budget, climate change, and air pollution. This study developed a multi-year (2001–2017), high-resolution (0.1° × 0.1°), monthly biomass burning emissions inventory covering all land types in tropical continents (Americas, Africa, and Asia). The emissions inventory was based on the updated MCD64A1 burned area product, MODIS fire radiative power (FRP) data, satellite and observational data of aboveground biomass density, spatiotemporal variable combustion efficiency, a conversion ratio, and emission factors. The results showed that the average annual emissions in tropical continents for 2001–2017 were 1.73 Tg BC, 10.85 Tg CH4, 261.41 Tg CO, 6083.69 Tg CO2, 3.60 Tg NH3, 39.75 Tg NMOC, 11.99 Tg NOx, 18.40 Tg OC, 29.63 Tg PM2.5, and 2.19 Tg SO2 . Taking CO2 as an example, woody savanna/shrubland fire was the largest contributor, accounting for 52% (3.16 × 10 3  Tg a −1 ) of total CO2 emissions, followed by fires in savanna/grassland (27%), forest (17%), cropland (3%), and peatland (1%). Africa was the largest emitter (3.77 × 10 3  Tg a −1 ), larger than Asia (1.20 × 10 3  Tg a −1 ) and the Americas (1.11 × 10 3  Tg a −1 ). The dominant fire types of vegetation burning were savanna/grassland in the Americas, woody savanna/shrubland in Africa, and forest in Asia. Moreover, biomass burning CO2 emissions exhibited considerable interannual variations, with high values in 2004, 2007, 2010, and 2015. Extensive savanna/grassland burning in the Americas in September and woody savanna/shrubland fires in Africa in August jointly led to peak CO2 emissions in August–September. This multi-year and high-resolution inventory for biomass burning emissions could be used in studies on global and regional biogeochemical circulation, atmospheric simulation, and air quality modeling. Graphical abstract: Image 1 Highlights: A multi-year and high-resolution biomass burning emissions inventory was developed. Annual CO2 emissions in Americas, Africa and Asia were 6083.69 Tg during 2001–2017. Woody savanna/shrubland was the largest contributor to the total CO2 emissions. Africa was the biggest emitter (62%) of CO2 emissions, larger than Asia and Americas. This inventory reduces uncertainties and could be used in air quality modeling.